PARADIGMA PENDIDIKAN DALAM ISLAM : Studi Surat Al-Alaq ayat 1 – 5 - Ifa Fathonah (Al-Fath, 2024)
Education in Islam has a deep theological and philosophical foundation, one of which can be found in Surah Al-Alaq verses 1-5. These verses, which were the first revelations revealed to the Prophet Muhammad (PBUH), provide an important guide to the basic principles of education in Islam. This research aims to describe the paradigm of Islamic education by examining the meaning and implications of Surah Al-Alaq verses 1-5. This study examines how the concepts of reading, human creation, and teaching through the pen as mentioned in these verses form the foundation of education that integrates intellectual, moral, and spiritual aspects. The results of the analysis show that the educational paradigm in Islam does not only emphasize intellectual development, but also emphasizes the importance of character formation based on awareness of the existence of Allah SWT and human responsibility as leaders on earth. In doing so, this research contributes to understanding how education in Islam should be designed to create intellectually and morally balanced individuals, who are able to face the challenges of modern times without losing their Muslim identity.